Effect of Hyperprolactinaemia on level of testosterone in a series of infertile Iraqi men - ABDUL KAREEM JABAR, ENAS (University of Thi-Qar Journal of Science, 2011)
The present study was designed to detect the level of testosterone due to by hyperprolactinaemia 20 patients, who were attending the civil laboratories in nassrya city for diagnosis and treatment the reasons of infertility during the period November 2008 – February 2010. Primary infertile males patients with hyperprolactinaemia (age range: 20 – 50 years) were investigated. The collected serum was tested for the determination of prolactin levels using a miniVidas system. (serum level of prolactin ≤19 ng/ml) , and were investigated level of testosterone the level was assayed sing a miniVidas system too serum level of testosterone ≥10 ng/ml the testosterone level showed a significant decreased total level in the sera of total patients when compared with controls and with hyperprolactinaemia patients.